The impact of centralized coronary stent procurement program on acute myocardial infarction treatments: evidence from China - Weiyan Jian; Wuping Zhou; Lanyue Zhang (Frontiers Media S.A., 2023)
BackgroundThe advent of coronary stents has resulted in many more many lives being saved from acute myocardial infarction (AMI). However, the high price associated with this method of treatment also imposes a heavy economic burden on healthcare systems. As a country making significant use of coronary stents, in 2021, China introduced a program around this method of treatment grounded in centralized procurement and it is the focus of this paper to assess the impact of this policy on AMI treatments.MethodsThe patients with AMI are selected as the study group, and the patients with pre-cerebral vascular stenosis are selected as the control group, and individual-level medical insurance settlement data are collected from the years 2018, 2019, and 2021. Differences-in-differences methodology is used to analyze the impacts of this program on the probability changes in respect of AMI patients receiving stent therapy, as well as changes relating to cost, length of stay and 30-day readmission.ResultsThe results show that the reform has led to a reduction in the probability of AMI patients using stents to 51% of the original rate. Additionally, the average cost is shown to have decreased by 41%, and no significant changes can be found in respect of the length of stay and 30-day readmission.ConclusionIn sum, the centralized procurement program is shown to reduce not only the medical expenses incurred by treating patients with AMI, but also the use of coronary stents, resulting in changes to the treatment patterns of patients with AMI.